2009
DOI: 10.1097/psy.0b013e3181bb2913
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Familias Unidas for Hispanic Adolescents With Behavior Problems

Abstract: Objective-To evaluate the efficacy of Familias Unidas, a Hispanic-specific, parent-centered intervention, in preventing/reducing adolescent substance use, unsafe sexual behavior, and externalizing disorders.Methods-A total of 213 8th grade Hispanic adolescents with behavior problems and their primary caregivers were assigned randomly to one of two conditions: Familias Unidas or Community Control. Participants were assessed at baseline and at 6, 18, and 30 months post baseline.Results-Results showed that, relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
184
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(188 citation statements)
references
References 47 publications
3
184
0
1
Order By: Relevance
“…One study (Pantin et al, 2009) was considered but not included because there was not an intervention effect on externalizing problems. Of note, no studies with children with ADHD or with ADHD symptoms as an outcome were identified as meeting all criteria.…”
Section: Resultsmentioning
confidence: 99%
“…One study (Pantin et al, 2009) was considered but not included because there was not an intervention effect on externalizing problems. Of note, no studies with children with ADHD or with ADHD symptoms as an outcome were identified as meeting all criteria.…”
Section: Resultsmentioning
confidence: 99%
“…The development of the parent curriculum, including issues of cultural sensitivity, are discussed in Bermudez Parsai, Castro, Marsiglia, Harthun, and Valdez (2011). It should be noted that the parenting measures, or similar ones, have been used in previous studies of parenting practices among Mexican-heritage parents (Pantin et al, 2009). …”
Section: Methodsmentioning
confidence: 99%
“…Parent communication can be thought of as an important part of monitoring the child’s behaviors, and prior research has shown that better parent-child communication (Fang, Schinke, & Cole, 2009; Martyn et al, 2009; Pantin et al, 2009; Tobler & Komro, 2010) serves as a protective factor against substance use behaviors among Hispanic adolescents. For example, Tobler and Komro (2010) found that Hispanic youths who are exposed to low levels of parental monitoring and limited communications were at a significantly greater risk for engaging in alcohol and marijuana use during the past year and month and at a greater risk of having ever smoked a cigarette.…”
Section: Introdutionmentioning
confidence: 99%
“…Six studies were found to have focused solely on the family for reducing adolescents' risk behavior with substance use Pantin et al, 2009;Schinke, Cole, & Fang, 2009;Schinke, Fang, & Cole, 2009;Spoth, Guyll, & Shin, 2009). However, one study ) that was categorized under combined intervention was also explained in family-based intervention and schoolbased intervention.…”
Section: Resultsmentioning
confidence: 98%